LO90: Predictors of post-concussion syndrome in adults with acute mild traumatic brain injury presenting to the emergency department: a secondary analysis of a randomized controlled trial. (May 2020) - Varner, C.; Thompson, C.; de Wit, K.; Borgundvaag, B.; Houston, R.; McLeod, S.
Abstract : Introduction: The emergency department (ED) is the first point of health care contact for most head injured patients. Although early and spontaneous resolution occurs in most patients with mild traumatic brain injury (MTBI), between 15-30% develop post-concussion syndrome (PCS). To date, clinical prediction tools do not yet exist to accurately identify adult MTBI patients at risk of PCS. The objective of this study was to identify predictors of PCS within 30 days in adults with acute MTBI presenting to the ED. Methods: This was a secondary analysis of a randomized controlled trial conducted in three Canadian EDs evaluating prescribed light exercise compared to standard care. Adult (18-64 years) patients with a MTBI sustained within the preceding 48 hours were eligible for enrollment. Participants completed follow-up questionnaires at 7, 14, and 30 days. The primary outcome was the presence of PCS at 30 days, defined as the presence of ≥ 3 symptoms on the Rivermead Post-concussion Symptoms Questionnaire (RPQ) at 30 days. Backward, stepwise, multivariable logistic regression with a removal criterion probability of 0.05 was conducted to determine predictor variables independently associated with PCS at 30 days. Likelihood ratio tests were used to determine appropriate inclusion of variables in the multivariable model. Results are reported as odds ratios (OR) with 95% confidence intervals (CIs). Results: A total of 367 patients were enrolled, 18 (4.9%) withdrew, and 108 (29.4%) were lost to follow-up. Median (IQR) age was 32 (25 to 48) years, and 201 (57.6%) were female. Of the 241 patients who completed follow-up, 49 (20.3%) had PCS at 30 days. Headache at ED presentation (OR = 6.59; 95% CI: 1.31 to 33.11), being under the influence of drugs or alcohol at the time of injury (OR = 4.42; 95% CI: 1.31 to 14.88), the injury occurring via bike or motor vehicle collision (OR = 2.98; 95% CI: 1.39 to 6.40), history of anxiety or depression (OR = 2.49; 95% CI: 1.23 to 5.03), and the sensation of numbness or tingling at ED presentation (OR = 2.25; 95% CI: 1.04 to 4.88), were independently associated with PCS at 30 days. Conclusion: Five variables were found to be significant predictors of PCS. Although MTBI is a self-limited condition in the majority of patients, patients with these risk factors should be considered high risk and flagged for early follow-up. There continues to be an urgent need for a clinical prognostic tool that accurately identifies adult patients at risk for PCS early in their injury.